A new species and a new combination in Tigridia (Tigridieae, Iridoideae, Iridaceae) from Oaxaca, Mexico - García-Mendoza, Abisaí; Sandoval Gutiérrez, Daniel (Instituto de Ecología, A.C., 2024)
Background and Aims: Tigridia sensu lato (Iridaceae) is an American genus with 52 species from Mexico and Guatemala; it belongs to Tigridieae, a monophyletic tribe endemic to America, which includes between 170 and 200 species. Botanical exploration in the state of Oaxaca allowed us to identify a new species for science; hence, the objective of this work was to name and describe it. Methods: Between 2018 and 2022, botanical collections of Tigridia were carried out in the municipality San Juan Teita, Tlaxiaco district, Oaxaca, whose morphological characteristics do not match with any previously known species. Therefore, it is formally described here and its relationships with the closest species are discussed. Its conservation status was assessed according to the categories and criteria of the IUCN Red List. Key results: Tigridia gypsicola is described and illustrated as a new species for science, endemic to the state of Oaxaca, and a new combination for T. conzattii var. macropetala (≡ Ainea conzattii var. macropetala) is presented. The new species is morphological compared with Tigridia coerulea and T. conzattii var. macropetala. According to the IUCN criteria, its restricted distribution, specialized habitat and diverse risk factors, the category of Vulnerable species (VU, D2) is proposed. Conclusions: The description of this new species increases the knowledge of the richness of Tigridia and represents new challenges for the circumscription of the genus. Its gypsophilous habit increases to ten the number of species of angiosperms restricted to this soil type in the municipality San Juan Teita, thus we consider it to be necessary to implement strategies for the conservation of this area.